Difficulties Faced by the Students of College of Arts in the Middle Euphrates Region in studying pre-Islamic Literature in Teachers’ Point of View - Al-Mamouri, Musa Kadhim Zqair (International Journal of Psychosocial Rehabilitation, 2020)
In order to clear this literary legacy and teaching methods for the researcher, A number of pre-Islamic literature met; and explained them some of the hardships and much of the difficulty of some words and structures because they are so strange that becomes difficult to pronounce and to understand their meanings, and this does not seem weird because there are some twisted figures of speech and structures that deviate from the normal grammatical patterns in pre-Islamic poetry. (Diaf, 1965 : p. 168). From what the researcher has looked through and the vision of Dr. Taha Hussein:" for me the old literature issue is like a long-standing garden, seems to be neglected continually however, life material has not cut it off, so its trees and bushes have been growing irregularly, this is the neglected and unstable growth, so that it gets mixed up severely. And it has become hard for you and those like you to find a way to what you like" (Hussein, 1974:p.19) The problem of teaching literature remains to be solved, teaching literature is still far from being performed well and achieving its objectives."(Friha, 1955:p.146 _147) "Our youth are not aware of their literary heritage, they are often unable to discriminate between what has been read from it and its aims. In addition to their vulnerability in emotions restraint and sentencing substantive provisions and their lack of artistic vision and aesthetics taste." (Al-Sayyid, 1980:p.188) Thus, the researcher dedicated themself to studying this phenomenon and to diagnosing problems facing students at this stage with the study of this subject, then identifying their causes and developing the proposed solutions to address them to serve as a basis you may find for it a place in the towering wall of literature. Describing their research problem with the following question: What are the difficulties experienced by pre-Islamic literature teachers in their teaching this subject?